Modulation of Cell Death by M. tuberculosis as a Strategy for Pathogen Survival. (20th December 2010) - Abebe, Markos; Kim, Louise; Rook, Graham; Aseffa, Abraham; Wassie, Liya; Zewdie, Martha; Zumla, Alimuddin; Engers, Howard; Andersen, Peter; Doherty, T. Mark
Abstract : It has been clearly demonstrated that in vitro, virulent M. tuberculosis can favor necrosis over apoptosis in infected macrophages, and this has been suggested as a mechanism for evading the host immune response. We recently reported that an effect consistent with this hypothesis could be observed in cells from the blood of TB patients, and in this paper, we review what is known about evasion strategies employed by M. tuberculosis and in particular consider the possible interaction of the apoptosis-inhibiting effects of M. tuberculosis infection with another factor (IL-4) whose expression is thought to play a role in the failure to control M. tuberculosis infection. It has been noted that IL-4 may exacerbate TNF- α -induced pathology, though the mechanism remains unexplained. Since pathology in TB typically involves inflammatory aggregates around infected cells, where TNF- α plays an important role, we predicted that IL-4 would inhibit the ability of cells to remove M. tuberculosis by apoptosis of infected cells, through the extrinsic pathway, which is activated by TNF- α . Infection of human monocytic cells with mycobacteria in vitro, in the presence of IL-4, appears to promote necrosis over apoptosis in infected cells—a finding consistent with its suggested role as a factor in pathology during M. tuberculosis infection.